Dress, fashion, and technology : from prehistory to the present - Tortora, Phyllis G. (London : Bloomsbury Academic, 2015)
"Technology has been an essential factor in the production of dress and the cultures of fashion throughout human history. Structured chronologically from pre-history to the present day, this is the first broad study of the complex relationship between dress and technology. Over the course of human history, dress-making and fashion technology has changed beyond recognition: from needles and human hands in the ancient world to complex 20th century textile production machines, it has now come to include the technologies that influence dress styles and the fashion industry, such as the media and printing presses. In the last century, new technologies have helped not just to produce but to define fashion: the creation of automobiles prompted a decline in long skirts for women while the beginnings of space travel caused people to radically rethink the function of dress. In many ways, technology has itself created avant garde and contemporary fashions. Through an impressive range of international case studies, the book challenges the perception that fashion is unique to western dress and outlines the many ways in which dress and technology intersect. Dress, Fashion and Technology is ideal reading for students and scholars of fashion studies, textile history, anthropology and cultural studies"--
Machine generated contents note: -- TABLE OF CONTENTS Chapter 1: Connecting Technology, Dress, And Fashion Part I, Before the Revolution, Chapter 2: Dress And The Technologies Of Prehistory (Upper Paleolithic To The Neolithic Period) Chapter 3: Technologies And Dress In Towns, Cities And Empires (Neolithic Period To C. 500 C.E.) Chapter 4: Technology And Dress Facilitate Fashion Change (Dark Ages to The Seventeenth Century in Europe) Chapter 5: Chapter 5: Some Asian Developments in Technology, Dress and Fashion (End of the Neolithic Period until the 17th Century) Part II: The Industrial Revolution and First Steps Toward the Fashion Industry Chapter 6: Dress And Fashion Move The Industrial Revolution Forward (18th Century) Chapter 7: The Central Role Of Dress And Fashion In The Industrial Revolution (c. 1800 to 1860) Chapter 8: Dress, Fashion And Social Changes Follow The Industrial Revolution (Nineteenth Century Chapter 9: Tools That Enable Fashion Change And Innovations In Dress (19th century) Part III, The Fashion Industry is Born Chapter 10: Tools And Processes Expand Options For Dress And Fashion (20th and 21st centuries) Chapter 11: Chapter 11: Transportation And Its Effects (20th and 21st centuries) Chapter 12: The Effects Of Sports (19th to the 21st centuries) Chapter 13 Communications Technologies That Disseminate Fashion Information (19th to the 21st centuries) Part IV, High Tech Enters Chapter 14 Chapter 14:Technology Contributes To The Globalization Of Fashion (20th and 21st centuries) Chapter 15: Environments Interact With Technologies (20th and 21st centuries) Chapter 16 New Technological Frontiers For Dress And Fashion (21st century) References Acknowledgements.
Includes bibliographical references and index.
Keywords: Clothing and dress -- History; DESIGN / Fashion; DESIGN / History & Criticism; Fashion design -- History; Tailoring -- History